Thermodynamic geometry, condensation and Debye model of two-parameter deformed statistics. (16th August 2017) - Mohammadzadeh, Hosein; Azizian-Kalandaragh, Yashar; Cheraghpour, Narges; Adli, Fereshteh
Abstract: We consider the statistical distribution function of a two parameter deformed system, namely qp -deformed bosons and fermions. Using a thermodynamic geometry approach, we derive the thermodynamic curvature of an ideal gas with particles obeying qp -bosons and qp -fermions. We show that the intrinsic statistic interaction of qp -bosons is attractive in all physical ranges, while it is repulsive for qp -fermions. Also, the thermodynamic curvature of qp -boson gas is singular at a specified value of fugacity and therefore, a phase transition such as Bose–Einstein condensation can take place. In the following, we compare the experimental and theoretical results of temperature-dependent specific heat capacity of some metallic materials in the framework of q and qp -deformed algebras.